Relationship between nutritional status and the incidence of anemia in adolescent women - Linda Puspita; Juwita Desri Ayu; Hamid Mukhlis (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Anemia is the ability of red blood cells to carry oxygen to other tissues is low (Onyeabo et al., 2017). The prevalence of adolescents in Lampung Province is 10.9% which is below the national prevalence (13.6%). The number of adolescents at SMPN 28 Bandar Lampung who had more Anemia was 64 students with HB less than 12 gr%, while SMPN 26 had fewer Anemia students with 26 students with HB less than 12 gr%. The purpose of this study was to determine the relationship between nutritional status and the incidence of anemia in adolescents in Public Junior High School 28 Bandar Lampung in 2021. This type of research is quantitative with a cross sectional approach. Research subjects were young women at SMPN 28 Bandar Lampung, with a sample of 93 respondents. The object of research is nutritional status and the incidence of anemia. The research was carried out at SMPN 28 Bandar Lampung. Data collection was carried out using observation sheets. Data analysis was carried out univariately and bivariately (gamma test). The results of the study revealed that 71 respondents with normal nutritional status (76.3%), Respondents with no incidence of anemia were 53 (57.0%). There is a relationship between nutritional status and the incidence of anemia in adolescents at SMP Negeri 28 Bandar Lampung in 2021 (p-value = 0.000). It is suggested that health workers can provide counseling about balanced nutrition or PUGS through schools and how to choose healthy food and health knowledge regarding adolescent reproductive health needs to be given as early as possible. Abstrak: Anemia adalah kemampuan sel darah merah untuk untuk membawa oksigen kejaringan lain rendah (Onyeabo at al., 2017). Prevalensi remaja di Provinsi Lampung terjadi 10.9% berada dibawah prevalensi nasional (13.6%).  Jumlah remaja SMPN 28 Bandar Lampung yang Anemia lebih banyak sejumlah 64 siswa HB kurang dari 12 gr %, sedangkan SMPN 26 jumlah remaja yang Anemia lebih sedikit sejumlah 26 siswa HB kurang dari 12 gr % Tujuan penelitian ini adalah diketahui hubungan status gizi dengan kejadian anemia pada remaja di Sekolah Menengah Pertama Negeri 28 Bandar Lampung Tahun 2021. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Subjek Penelitian remaja putri di SMPN 28 Bandar Lampung, dengan sampel sebanyak 93 responden. Objek penelitian status gizi dan kejadian anemia.Penelitian telah dilaksanakan di SMPN 28 Bandar Lampung. Pengumpulan data dilakukan menggunakan lembar observasi.Analisis data dilakukan univariat dan bivariat (uji gamma). Hasil penelitian diketahui reponden dengan status gizi normal sebanyak 71 (76,3%), responden dengan tidak kejadian anemia sebanyak 53 (57,0%). Ada hubungan status gizi dengan kejadian anemia pada remaja di Sekolah Menengah Pertama Negeri 28 Bandar Lampung Tahun 2021 (p-value = 0,000). Saran tenaga kesehatan dapat memberikan penyuluhan tentang gizi seimbang atau PUGS melalui sekolah dan cara memilih makanan yang sehat dan pengetahuan kesehatan mengenai kesehatan reproduksi remaja perlu diberikan sedini mungkin